Suggestions for an East Asian Monetary Union: Focusing on the Effects of Monetary Integration on Bilateral Trade - Min-Chang Ko; Byung-Taik Cho (East Asian Economic Review, 2006)
This study explores alternative ways toward the East Asian monetary union, focusing on the effect of monetary integration on bilateral trade. For this purpose, we analyze with gravity model changes of the bilateral trade among countries of EU, NAFTA, and East Asia. A distinctive feature of this model is that it includes the dummy variables that show the cultural intimacy among North-East Asian countries, Asian NIEs countries, and East Asian countries (North-East Asian and ASEAN countries). We discovered that bilateral trade increased at a highest level among East Asian countries than the other two cases. This result suggests that the once-and-for-all strategy to develop an East Asian monetary union including North-East Asian and ASEAN countries would be more efficient than the multitrack strategy that forms the monetary union of North-East Asian countries in the first place and then tries to extend it to ASEAN countries.